DESIGN OF ELECTRICALLY RECONFIGURABLE MICROSTRIP BASED BANDPASS FILTER - YOON, CHIEK XIN (IRC, 2019)
Microwave filters are important components in vary electronic systems, for example satellite communications, cellular radio and radar. Microstrip is a type of electrical transmission line or filter technology that is fabricated on printed circuit board (PCB) which is use to convey microwave frequency signals. Microstrip is less expensive, lighter and compact compare to the traditional waveguide and coaxial cable. A reconfigurable microstrip based bandpass filter is an electrical transmission line which the bandwidth and the center frequency and can be vary continuously are essential. Reconfigurable filters are an excellent solution for many military and commercial applications because of its ability to vary the bandwidth and center frequency of radio frequency system continuously without requiring filter banks that support multiple frequency with switch which is bulky and expensive. A series of mathematical calculations are conducted for modelling of electrically reconfigurable microstrip based bandpass filter. Next, the design of ideal and microstrip circuit simulated in ADS software have a good agreement. The results of reflection coefficient, S11 is less than 15dB in the passband. Then, varactor modeling of SMV1247-079LF is conducted. The varactor diode gives capacitance of 2.11 pF to 1.74 pF while supplying 1.89 V to 2.06 V reversed voltage. Reconfigurable microstrip based bandpass filter is achieved by using SMV1247-079LF varactor diode as tuning element to vary the center frequency from 980 MHz to 1020 MHz while varying the supplied reversed voltage and capacitance of varactor diode from 2.11 pF to 1.74 pF and 1.89 V to 2.06 V respectively. The scope of study of this project includes designing the parameters for an electrically reconfigurable microstrip based bandpass filter uses varactor diodes as tuning elements. On the other hand, the scope of study also includes the variation of capacitance value of varactor diode when different reverse bias voltage is applied. In order to complete the project by achieving all the objectives, research methodology and prototype design flow is constructed.